Die zeitweise Verlagerung von Arbeitskräften in die Arbeitslosigkeit: eine "neue" personalpolitische Flexibilisierungsstrategie? - Stefan Liebig; Andrea Hense (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
– In the German debate on firms' flexibility strategies, one strategy for handling the fluctuation of labour requirements is mainly ignored: the temporary laying off of employees and their subsequent reemployment by the same employer (recalls). This paper focuses on describing the extent of recalls in Germany and analysing their determinants. The main hypothesis is that even in Germany recalls are a firm-specific strategy to respond to cyclical labour demands, which is not restricted to certain sectors or branches. In order to demonstrate this, recalls are located in the context of strategies used by German firms to adjust their cyclical demand for labour. The paper then discusses why it is rational both from the viewpoint of a single firm and from the viewpoint of laid-off workers to implement recalls and to wait to be rehired and what external conditions are necessary for using recalls as a personnel strategy. The results are based on the linked employer-employee dataset (LIAB) of the Institute for Employment Research (IAB) and support the assumption of a firm-specific use of recalls. Furthermore, they show that employees who are reemployed by their former employer gain income advantages. Finally, the relevance of the results is discussed against the background of the current debate about flexibility strategies and topics for further research are indicated.
Keywords: 330; vorübergehende Entlassungen; betriebsbedingte Kündigung; Wiederbeschäftigung - Determinanten; Beschäftigungssystem - Flexibilität; Personalanpassung; IAB-Linked-Employer-Employee-Datensatz; Konjunkturzyklus; Lohnhöhe; Unternehmensgröße; Beschäftigtenstruktur; Qualifikationsstruktur